Characterisation of the murine CLK1 dual-specificity kinase. - Duncan, Peter I. (University of Ottawa (Canada), 1997)
Murine Clk1 (also known as Sty) was identified as a dual-specificity kinase capable of phosphorylating serine, threonine and tyrosine residues when expressed in bacteria. Expression of Clk1 is deveolpmentally regulated at the level of RNA expression. Embryonic cells express two mRNAs of similar size, whereas differentiated cells express two additional transcripts of larger size. Little is known about the bochemical and biological activity of Clk1 in mammalian cells. We demonstrate that the two embryonically expressed mRNAs are derived through alternative splicing of a unique exon (exon EB) within the Clk1 precursor mRNA. These mRNAs encode full-length catalytically active Clk1 and a truncated inactive polypeptide, Clk1$\rm\sp{T}.$ Larger incompletely spliced Clk1 transcripts accumulate in differentiated cells. When expressed in mammalian cells Clk1 possesses dual-specificity kinase activity and is capable of forming complexes with other molecules of Clk1 and Clk1$\rm\sp{T}.$ The regions involved in binding map to the amino-terminal non-catalytic domain of Clk1. Phosphorylation sites map to the amino acids encoded by the alternatively splice exon EB. Clk1$\rm\sp{T}$ and catalytic mutants of Clk1 co-localise with splicing factors in intranuclear speckles, whereas catalytically active Clk1 causes a redistribution of these factors within the nucleus. This activity requires the presence of amino acids encoded by exon EB. These results suggest a role for Clk1 and Clk1$\rm\sp{T}$ in the regulation of RNA splicing. Splicing of a Clk1 mini-gene, encompassing exon EB, in vivo is regulated by Clk1 and Clk1$\rm\sp{T}.$ Catalytically active Clk1 stimulates exclusion of EB leading to the production of Clk1$\rm\sp{T}$ mRNA. In contrast, Clk1$\rm\sp{T}$ promotes EB inclusion leading to production of Clk1 mRNA. Two Clk1-related human kinases, hClk2 and hClk3, also exhibit dual-specificity kinase activity and cause the redistribution of nuclear splicing factors. Similar to Clk1$\rm\sp{T},$ the hClk truncated isoforms, hClk2$\rm\sp{T}$ and hClk3, co-localise with splicing factors in nuclear speckles. hClk2 and hClk3 are able to influence the splicing pattern of a murine Clk1 mini-gene in vivo, indicating that they can also regulate precursor mRNA splicing. Taken together these results imply a role for the Clk family of kinases in the regulation of gene expression at the level of RNA processing.
Keywords: Biology, Molecular.